The demographics of nuclear power: Comparing nuclear experts', scientists' and non-science professionals' views of risks, benefits and values. (December 2018) - Harris, Jill; Hassall, Maureen; Muriuki, Grace; Warnaar-Notschaele, Celestien; McFarland, Eric; Ashworth, Peta
Highlights: Nuclear experts, who were more knowledgeable on nuclear energy and had more first-hand experience with nuclear energy, were more active in seeking out information on and had more favourable attitudes towards the use of nuclear energy and perceived there to be fewer risks in its use compared to STEM and non-STEM professionals. Values and beliefs about human–environment interaction and perceived benefits of nuclear energy did not significantly differ across nuclear experts, STEM and non-STEM professionals. Levels of trust in the nuclear industry did not significantly differ between nuclear experts and STEM professions. Similar to outcomes of prior studies with laypersons, the current study found that across all professional groups trust in the nuclear industry, perceived risks and benefits, as well as personal norms and values, influenced attitudes towards nuclear energy. Also, across all professional groups perceived benefits were found to have a more influential role on attitudes towards nuclear energy than perceived risks. Abstract: Science, technology, engineering and mathematics (STEM) professionals can play an influential role in guiding other people's views of nuclear energy. There has been limited recent research to understand STEM professionals' attitudes towards nuclear and how they might vary. The present study measured these groups' attitudes towards nuclear energy as well as their perceptions regarding known determinants of attitudes – including trust in nuclear agencies, appraisals of risk and benefits of nuclear energy, and associated environmental values. Strict criteria were used to identify nuclear experts and STEM professionals. To drill deeper on the determinants of professionals' perceptions of nuclear energy, this study also investigated the determinants of attitudes towards nuclear energy, when age, gender and professional status were held constant. The STEM professionals perceived nuclear energy to have more negative consequences than did nuclear experts, but less than non-STEM professionals. Levels of trust in the nuclear industry did not significantly differ between the STEM professional and nuclear expert groups, nor did perceived benefits or environmental impacts of nuclear energy. Gender, trust, perceived risk and benefits and environmental values contributed to acceptance of nuclear energy. The most influential of these were trust in the nuclear industry and perceived benefits of nuclear energy.